PENGARUH LATIHAN X-PATTERN MULTI SKILL TERHADAP KELINCAHAN SISWA SSB RUMBAI PRATAMA PEKANBARU - Wibowo, Galih Agung Wibowo Agung; Wijayanti, Ni Putu Wijayanti Putu; ', Saripin Saripin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This research was conducted to determine whether there are effects of exercise on the x-pattern multi skill against the agility on the soccer school students so that when players can move agility in all direction to the maximum results. The method is experimental research mehtod and population is SSB Rumbai Pratama Pekanbaru with a sample 22 students. Sampling technique that the overall population.The instrument used in this reseach is illinois agility test, which aims to measure the agility of student soccer SSB Rumbai Pratama Pekanbaru. Afterthat, the data is processed with statistics, with test normality test at a significant level 0,05α lilifors. Hypothesis, there are significant effects of exercise the x-pattern multi skill against agility. Based on the analysis of statistical data, there are at Pree-test average was 16,78 and post-test average was 15,99 the data is normal. Based on t test analysis produced Tcount 4.11 and Ttable 1.721, meaning that Tcount > Ttable. Then, there is the Securities Exercise x-pattern multi skill against the agility on the football players in SSB Rumbai Pratama Pekanbaru.Keywords: X-Pattern Multi Skill, Agility